Prime Minister and Cabinet in Canada: An Autocracy in Need of Reform? - Bakvis, Herman (Journal of Canadian Studies, 2000)
It has been suggested that the Canadian prime minister tends to enjoy powers to a degree that is unhealthy in a democratic society. This article evaluates the "prime minister as autocrat" argument that has gained currency, if not in the academic literature, certainly in the popular media. It is suggested that while there has been a relative increase in the concentration of power in the centre — the centre defined as the prime minister, his entourage and key central agencies — the portrait of prime ministerial autocracy has been overdrawn. None the less, reforms are desirable. Particularly ones that create or enhance counterweights to prime ministerial power will likely improve Canadian democracy. These reforms should focus not so much on strengthening the role of individual MPs but on reinforcing the position of cabinet, the parliamentary caucus and senate vis-à-vis the prime minister. In this respect, five possible reforms are discussed, and their prospects of being adopted assessed: proportional representation for the House of Commons, an elected senate, strengthened parliamentary caucuses, a fixed time-table for elections and the New Zealand approach to the appointment of senior officials.